2019
DOI: 10.2147/cmar.s195413
|View full text |Cite
|
Sign up to set email alerts
|

<p>Role of the pretreatment neutrophil-to-lymphocyte ratio in the survival of primary parotid cancer patients</p>

Abstract: Background: To analyze the value of the pretreatment neutrophil-to-lymphocyte ratio (NLR) in the survival of patients with parotid cancer. Methods: In total, 249 patients were enrolled. Information including age, sex, pretreatment NLR, and pathologic variables such as, tumor stage, intraparotid node (IPN) metastasis, and follow-up findings was extracted and analyzed. Results: IPN metastasis was noted in 45 (18.1%) patients, and the mean NLR was 2.48, with a range from 1.5 to 6.1. The NLR was significantly asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 33 publications
(58 reference statements)
2
23
0
2
Order By: Relevance
“…The association between the NLR and clinical pathologic variables has been described by previous studies in head and neck cancer (19,20,23). Our previous studies reported that a high NLR was related to advanced disease stage, poor differentiation, and advanced lymph node stage in parotid cancer (19,20).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The association between the NLR and clinical pathologic variables has been described by previous studies in head and neck cancer (19,20,23). Our previous studies reported that a high NLR was related to advanced disease stage, poor differentiation, and advanced lymph node stage in parotid cancer (19,20).…”
Section: Discussionsupporting
confidence: 61%
“…A recent meta-analysis concluded that an elevated NLR was predictive of poorer overall survival in patients with HNSCC (15). Our previous research also showed that a high NLR was associated with worse prognosis in locally advanced tongue SCC (20). However, none of the abovementioned studies evaluated the p16-negative SCC of unknown primary; thus, this study was the first to note that compared with patients in the other two subgroups, patients with an NLR > 6.0 had the worst prognosis.…”
Section: Discussionmentioning
confidence: 63%
“…The NLR was calculated within 2 weeks before the initial treatment by the ratio of the absolute neutrophil count to the absolute lymphocyte count (14)(15)(16)(17)(18)(19)(20)(21). The previous reported cutoff values varied from 1.98 to 5 (14)(15)(16)(17)(18)(19)(20), and the standard cutoff value remains unknown. The cutoff value was defined as the mean value of the NLR in current study.…”
Section: Methodsmentioning
confidence: 99%
“…16 Damar ve ark., Cheng ve ark., Kawakita ve ark., Seng ve ark., ile Kuzucu ve ark.nın yaptıkları çalışmalarda, NLR ve PLR'yu malign lezyonlarda daha yüksek olarak saptanmıştır. 1,15,[17][18][19] Malign parotis tümörlü hastalarda, benign parotis tümörlü hastalara göre yüksek NLR, yüksek nötrofil yüzdesi, düşük lenfosit sayısı ve düşük lenfosit yüzdesi saptanmıştır. NLR ve lenfosit yüzdesi kombinasyonunun düşük ve yüksek gradeli tümörleri ayırt etmede bir belirteç olarak kullanılabileceği tespit edilmiştir.…”
Section: Bulgularunclassified
“…Bu sonuçlar, NLR'nin parotis tümörlerinde hastalıksız sağkalım için bağımsız prognostik faktör olduğunu düşündürmektedir. 17 Çalışmamızda da NLR seviyesi benign tümörlerde 1,84, malign tümörlerde 2,68; PLR seviyesi benign tümörlerde 114,26, malign tümörlerde 153,44 olarak tespit edilmiştir. Kesim noktası NLR için 2,13, PLR için 126,75 tespit edilmiştir.…”
Section: Bulgularunclassified